2009
DOI: 10.1097/ccm.0b013e31819fffd3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic benefits of surface counter warming during therapeutic temperature modulation*

Abstract: Surface CW provides beneficial control of shivering and improves the metabolic profile during TTM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 30 publications
0
58
0
2
Order By: Relevance
“…Possible explanations for the lack of shivering in our patient group might be the small covered area by the neck pads, the small amount of temperature decline and analgosedation in most of the patients. Furthermore, in all our patients serum magnesium levels were close to the upper limit [18], following our standard treatment protocol of aSAH [17]. Despite concerns of an accidental obstruction of the jugular venous drainage or triggering of autonomous dysfunctions via vulnerable structures like the glossopharyngeal and vagal nerves or carotid bodies, we did not observe any relevant changes concerning these issues during the study period after application of the neck pads.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Possible explanations for the lack of shivering in our patient group might be the small covered area by the neck pads, the small amount of temperature decline and analgosedation in most of the patients. Furthermore, in all our patients serum magnesium levels were close to the upper limit [18], following our standard treatment protocol of aSAH [17]. Despite concerns of an accidental obstruction of the jugular venous drainage or triggering of autonomous dysfunctions via vulnerable structures like the glossopharyngeal and vagal nerves or carotid bodies, we did not observe any relevant changes concerning these issues during the study period after application of the neck pads.…”
Section: Discussionmentioning
confidence: 74%
“…Side effects were defined as skin irritation, pressure marks, wound infection, disturbances in wound healing of a new tracheostomy, or shivering. Shivering, defined as involuntary, oscillatory muscular activity, and cutaneous vasoconstriction [18] was assessed together with each taken temperature value at fixed times as mentioned above and documented as absent, mild, or severe. Changes of the analgetic or sedative medication, changes in arterial blood pressure, and heart rate were documented at least hourly following the standard treatment protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Nonpharmacological interventions [12][13][14]29,30 (Table 3) such as skin warming reduce the vasoconstriction and shivering thresholds because the thresholds are negatively and linearly related to skin temperature. 9 Skin counterwarming techniques are thought to be effective because mean skin temperature represents approximately 20% of the total regulatory input.…”
Section: Nonpharmacological Methodsmentioning
confidence: 99%
“…Nonpharmacological methods have had limited use in hospitals. However, research [12][13][14][15] has shown that the use of skin counterwarming techniques is beneficial as an adjunct therapy in the management of shivering during therapeutic hypothermia.…”
Section: Management Of Shivering During Therapeutic Hypothermiamentioning
confidence: 99%
“…13 Additionally, interobserver reliability is high in patients being actively cooled after stroke. 22 Thus, the BSAS has potential utility as a clinical and research tool for the evaluation of shivering in the setting of TTM.…”
mentioning
confidence: 99%